Genome-wide analysis of pain-, nerve- and neurotrophin -related gene expression in the degenerating human annulus - Gruber Helen E; Hoelscher Gretchen L; Ingram Jane A; Hanley Edward N (SAGE Publishing, 2012)
Abstract Background In spite of its high clinical relevance, the relationship between disc degeneration and low back pain is still not well understood. Recent studies have shown that genome-wide gene expression studies utilizing ontology searches provide an efficient and valuable methodology for identification of clinically relevant genes. Here we use this approach in analysis of pain-, nerve-, and neurotrophin-related gene expression patterns in specimens of human disc tissue. Control, non-herniated clinical, and herniated clinical specimens of human annulus tissue were studied following Institutional Review Board approval. Results Analyses were performed on more generated (Thompson grade IV and V) discs vs. less degenerated discs (grades I-III), on surgically operated discs vs. control discs, and on herniated vs. control discs. Analyses of more degenerated vs. less degenerated discs identified significant upregulation of well-recognized pain-related genes (bradykinin receptor B1, calcitonin gene-related peptide and catechol-0-methyltransferase). Nerve growth factor was significantly upregulated in surgical vs. control and in herniated vs. control discs. All three analyses also found significant changes in numerous proinflammatory cytokine- and chemokine-related genes. Nerve, neurotrophin and pain-ontology searches identified many matrix, signaling and functional genes which have known importance in the disc. Immunohistochemistry was utilized to confirm the presence of calcitonin gene-related peptide, catechol-0-methyltransferase and bradykinin receptor B1 at the protein level in the human annulus. Conclusions Findings point to the utility of microarray analyses in identification of pain-, neurotrophin and nerve-related genes in the disc, and point to the importance of future work exploring functional interactions between nerve and disc cells in vitro and in vivo. Nerve, pain and neurotrophin ontology searches identified numerous changes in proinflammatory cytokines and chemokines which also have significant relevance to disc biology. Since the degenerating human disc is primarily an avascular tissue site into which disc cells have contributed high levels of proinflammatory cytokines, these substances are not cleared from the tissue and remain there over time. We hypothesize that as nerves grow into the human annulus, they encounter a proinflammatory cytokine-rich milieu which may sensitize nociceptors and exacerbate pain production.